Outcomes comparison of IVF/ICSI among different trigger methods for final oocyte maturation: A systematic review and meta‐analysis. Issue 7 (3rd June 2021) - Zhang, Yu; Guo, Xiaoyan; Guo, Linjiang; Chang, Hsun‐Ming; Shu, Jing; Leung, Peter C. K.
Abstract: During the in vitro fertilization treatment, human chorionic gonadotrophin (hCG) is routinely used as a substitute for the natural endogenous LH surge during the final stage of oocyte maturation. However, it does not provide the FSH surge observed in the mid‐cycle of the natural cycle. To date, whether the FSH surge can improve oocyte quality and pregnancy outcomes remains unknown. Randomized controlled trials comparing the following four trigger methods to conventional hCG were examined: GnRH agonist (GnRHa), kisspeptin, GnRHa plus hCG (dual trigger), and FSH plus hCG (FSH co‐trigger). The results showed that the use of dual triggers was associated with a significantly higher number of retrieved cumulus‐oocyte complexes (COCs) (weighted mean difference [WMD] 1.625, 95% CI 0.684‐2.565), retrieved mature oocytes (WMD 0.986, 95% CI 0.426‐1.545) and fertilized (2PN) oocytes (WMD 0.792, 95% CI 0.083‐1.501), compared with the use of hCG. However, there was no significant difference between the two groups in terms of pregnancy rate. The FSH co‐trigger resulted in significantly higher rates of 2PN oocytes retrieved than the hCG trigger (WMD 0.077, 95% CI 0.028‐0.126). Notably, the risk of OHSS did not differ among the three treatment groups compared to that of the hCG group. This review protocol was registered with PROSPERO (CRD 42020194201).